Impact of diabetes on the effects of sodium glucose co-transporter-2 (SGLT2) inhibitors on kidney outcomes: collaborative meta-analysis of large placebo-controlled trials - Herrington, W; Staplin, N; Haynes, R; Mayne, K; Roddick, A; Landray, M; Baigent, C; Preiss, D; Judge, P; Emberson, J (Elsevier, 2022)
Background: Large trials have shown that sodium glucose co-transporter-2 (SGLT2) inhibitors reduce the risk of adverse kidney and cardiovascular outcomes in patients with heart failure or chronic kidney disease, or with type 2 diabetes and high risk of atherosclerotic cardiovascular disease. None of the trials recruiting patients with and without diabetes were designed to assess outcomes separately in patients without diabetes.